Defaunation changes leaf trait composition of recruit communities in tropical forests in French Guiana. Issue 1 (27th November 2022) - Vaessen, Rens W.; Jansen, Patrick A.; Richard‐Hansen, Cécile; Boot, René G. A.; Denis, Thomas; Derroire, Géraldine; Petronelli, Pascal; de Vries, Jesse S.; Barry, Kathryn E.; ter Steege, Hans; van Kuijk, Marijke
Abstract: Hunting impacts tropical vertebrate populations, causing declines of species that function as seed dispersers and predators, or that browse seedlings and saplings. Whether and how the resulting reductions in seed dispersal, seed predation, and browsing translate to changes in the tree composition is poorly understood. Here, we assess the effect of defaunation on the functional composition of communities of tree recruits in tropical rainforests in French Guiana. We selected eight sites along a gradient of defaunation, caused by differences in hunting pressure, in otherwise intact old‐growth forests in French Guiana. We measured shifts in functional composition by comparing leaf and fruit traits and wood density between tree recruits (up to 5 cm diameter at breast height) and adults, and tested whether and how these compositional shifts related to defaunation. We found a positive relationship with defaunation for shifts in specific leaf area, a negative relationship for shifts of leaf toughness and wood density, and a weak relationship for shifts in fruit traits. Our results suggest that the loss of vertebrates affects ecological processes such as seed dispersal and browsing, of which browsing remains understudied. Even though these changes sometimes seem minor, together they result in major shifts in forest composition. These changes have long‐term ramifications that may alter forest dynamics for generations.